THE CRIME OF HIRABAH: APPROACH, JUSTIFICATION AND SIGNIFICANCE - Md Asri, Muhammad Hameedullah; Ruslan, Md Khalil (Jurnal Syariah, 2020)
The punishment for ḥirābah as a ḥadd crime has been prescribed by the Lawmaker in the Qurʻān, in Chapter al-Mā’idah, 33. The provision stipulates four types of punishment, namely; execution, cutting off of hands and feet, crucifixion and banishment. Despite ḥirābah being a serious crime and the only ḥadd crime with four punishments, al-Mā’idah 33 is completely silent about the meaning of ḥirābah, its constituent elements, modes of crime and conditions. This has led the crime being approached either through a restrictive or a permissive manner by Muslim scholars. The objective of this paper is to study the concept of ḥirābah from both perspectives, their justifications and significant impacts on possible application of Islamic criminal law on the subject. This is carried out through careful examination of literature contributed by both classical and modern times. The findings of the study suggest that the restrictive approach considers ḥirābah to be a crime of highway robbery – grave theft – while the permissive approach does not stipulate any particular designation to the crime. Ḥirābah to the latter is of an unlimited crime. Their justifications range from textual to contextual analyzes, application of qiyās and other principles of Islamic jurisprudence. The significant impacts of both approaches are seen on the possible application of ḥirābah; either being a strict or a flexible form of crime, a limited or an unlimited with specified or unspecified types of punishment, involving the application of two witnesses or otherwise and the effect of repentance.